Perancangan Keamanan Akses Internet Berbasis Text Filtering Pada Universitas Atma Jaya Makassar - Harry Susanto Wirawan (Fakultas Teknologi Informasi, Universitas Atma Jaya Makassar, 2021)
University of Atma Jaya Makassar has good internet access that can be used by everyone in the environment. From the observations, it is known that networks that can be accessed openly have not yet been handled to filter content on a website. Starting from this, the researcher intends to design a proxy server that can handle filtering text content and also optimizes internet access security on UAJM. The results of this study showed that sites categorized as pornography and radicalism are taken at random and then evaluated giving result of 74.9% for pornographic websites and 20.1% for radicalism websites.